Analisis Kinerja Karyawan Ground Handling Ditinjau Dari Tingkat Kedisiplinan Pada Pt Kokapura Avia Bandar Udara Yogyakarta Internasional Airport Kulonprogo - Ashila Afriyati Wardha; Andityo Pujo Laksana (CV. Aksara Global Akademia, 2023)
The level of discipline on the performance of ground handling employees is very important, discipline is also needed in improving employee performance. The basic attitude of employees towards themselves, competencies and current job as well as an overview of every opportunity that can be achieved needs to be considered by PT Kokapura Avia Yogyakarta International Airport. Performance analysis of ground handling employees will discuss how ground handling employee performance that viewed from the level of discipline based on the performance indicator. This research uses a qualitative research method design, which data collection is carried out by interviews, observation, documentation, and literature studies in the work area of the passasi unit of PT Kokapura Avia Yogyakarta International Airport. This research was conducted to determine the performance of ground handling employees in terms of the level of discipline at PT Kokapura Avia Yogyakarta Internasional Airport. The results of this study are the performance of ground handling employees on time is quite good in providing services to passangers, ground handling employees are quite good in two ways communication between leaders and subordinates, ground handling employees obey the regulations in accordance with standard operating procedures (SOP), carry oud good cooperation with coworkers, creating a sense of comfort and safety at work has improved well.